ENHANCING THE STUDENTS’ FLUENCY IN WRITING THROUGH THE USE OF JOURNAL WRITING - Nor Jannah (LET: Linguistics, Literature and English Teaching Journal, 2013)
Writing in English claimed as the hardest skill to be achieved by the students, especially the students at STAI Darul Ulum Kandangan because of some reasons.  The reasons are because the students have no ideas to write, they have very limited vocabulary, and they are not sure with their grammar.  However, those kinds of reasons can be solved by using journal writing focusing only on the fluency of writing performed by the students.